Perancangan Tempat Tidur Multifungsi untuk Apartemen Tipe Studio - Melissa Christany; Lintu Tulistyantoro; Grace Setiati Kattu (Intra, 2018)
The room of studio apartment is relatively smaller than the 2 or 3 rooms apartment, where is the space only for bedroom and bathrooms. Bedroom is also used for living room, dining room, work space and kitchen. User in their activities sometimes has guests in the room, but there is no place to accommodate it. The effect, bed as a private for user used by guests too, and guests feel not comfortable to use. The purpose of designing furniture with more functions, characters and shapes that are useful to accommodate a wide range of workspaces. The method stages of this design is empathize, define, ideate, prototype and test. Multifunction bed as a place to rest, receive guests, work, eat, discuss and store items can help the needs of users.